Matemática, perguntado por dudarochaandrad, 1 ano atrás

responda  a equacao :
a) (1 + a)³
b) (x - 2y)³
c) (2x + 3)³

Soluções para a tarefa

Respondido por alexandre11000
1
a) (1 + a).(1 + a).(1 + a)=
    (1 + a + a + a²) = (1 + 2a + a²) =
    (1 + 2a + a²).(1 + a) =
    (1 + a + 2a + 2a² + a² + a³) = a³ + 3a² + 3a + 1
então: (1 + a)³ = a³ + 3a² + 3a + 1


b) (x - 2y).(x - 2y) =
   (x² - 4xy + 4y²).(x - 2y) =
   (x³ - 2x²y - 4x²y + 8xy² + 4xy² - 8y³) = x³ - 6x²y + 12xy² - 8y³

c) (2x + 3).(2x + 3) =
    (4x² + 12x + 9).(2x + 3) =
    (8x³ + 12x² + 24x² + 36x + 18x + 27) = 8x³ + 36x² + 54x + 27
Perguntas interessantes